Penerapan Asas Ultra Petitum Partium Dalam Perkara Cerai Talak Peradilan Agama di Kabupaten Sleman: Studi Kasus Putusan Perkara Nomor 1086/PDT.G/2024/PA.SMN - Dharmasanti Rawidya Putri; Sigit Wibowo (Prosiding Seminar Nasional Ilmu Hukum, 2025)
This study has two main objectives: first, to analyze the application of the principle of ultra petitum partium in talaq divorce cases based on the Decision of the Sleman Religious Court Number 1086/Pdt.G/2024/PA. Smn; Second, to examine the basis of judges' legal considerations in determining matters that are not explicitly requested, especially from the perspective of the protection of the rights of the wife. This study uses a normative juridical method with a case approach and a statute approach. The results of the study show that the provision of iddah maintenance by the judge based on the mediation agreement of the parties does not violate the principle of ultra petitum partium. However, the determination of mut'ah in the absence of an explicit request in the petitum has the potential to be contrary to this principle. However, the judge's actions can be justified through ex officio authority in order to protect the rights of the wife, in accordance with Article 158 of the Compilation of Islamic Law. These findings highlight the tension between procedural legal certainty and substantive justice in the religious justice system. This study recommends that judges explicitly state legal grounds when exercising ex officio authority, to ensure transparency and accountability in decisions.